Simplified and shortened French adaptation of a self-esteem contingency measure - Martin Robion; Sophie Berjot; Manon Balty; Céline Stinus; Kwamigan Ahondo; Charly Marie; David Bourguignon (Frontiers in Psychology)
IntroductionThis study aims to validate a shortened and adapted French version of a self-esteem contingency measure specifically designed to evaluate how self-esteem depends on two fundamental psychological needs: competence and affiliation. To ensure a clear understanding and broaden the tool's validity across diverse populations, it was tested among three groups: students, job seekers, and employees.MethodsFour samples participated in the survey: students (N = 221, N = 507), job seekers (N = 270), and employees (N = 328). Participants completed the adapted self-esteem contingency scale along with other selected scales to assess convergent and discriminant validity. Exploratory factor analysis (EFA) and confirmatory analyses (CFA, ESEM, Bifactor-CFA, and Bifactor-ESEM) were conducted to explore the scale's structure.ResultsThe EFA revealed a two-dimensional structure, while the confirmatory analyses suggested a bifactorial model composed of one global factor and three specific factors: contingency regarding competence, self-criticism, and contingency regarding relationships. The bifactorial model demonstrated good internal consistency across all groups and satisfactory temporal stability. Correlation analyses with other constructs supported the convergent and discriminant validity of the scale.ConclusionOverall, the shortened and adapted French version of the self-esteem contingency measure is a valid and reliable instrument. It assesses global self-esteem contingency while accounting for the specificities related to the needs for competence and affiliation. This dual focus enhances the scale's applicability in both research and intervention contexts.